2021
DOI: 10.1155/2021/4303380
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Qingfei Paidu Decoction on Patients with COVID-19 Pneumonia in Wuhan, China: A Propensity Score Matching Study

Abstract: Background. In view of the global efforts to develop effective treatments for the current worldwide coronavirus 2019 (COVID-19) pandemic, Qingfei Paidu decoction (QPD), a novel traditional Chinese medicine (TCM) prescription, was formulated as an optimized combination of constituents of classic prescriptions used to treat numerous febrile and respiratory-related diseases. This prescription has been used to treat patients with COVID-19 pneumonia in Wuhan, China. Hypothesis/Purpose. We hypothesized that QPD woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…After eliminating duplicates, the titles, abstracts and full text of 279 records were screened. Finally, we included 9 studies with 1108 COVID-19 patients ( Chen et al, 2021 ; Li et al, 2020 ; Li and Zhang, 2020 ; Liu et al, 2021b ; Wang et al, 2021a ; Xin et al, 2020 ; Yu et al, 2020b ; Zeng et al, 2020 ; Zhang and Pan, 2021 ). WMT in each study were shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After eliminating duplicates, the titles, abstracts and full text of 279 records were screened. Finally, we included 9 studies with 1108 COVID-19 patients ( Chen et al, 2021 ; Li et al, 2020 ; Li and Zhang, 2020 ; Liu et al, 2021b ; Wang et al, 2021a ; Xin et al, 2020 ; Yu et al, 2020b ; Zeng et al, 2020 ; Zhang and Pan, 2021 ). WMT in each study were shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The screening process was shown in Figure 1 . Seven papers were published in Chinese and two in English ( Liu et al, 2021b ; Xin et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations